2019
DOI: 10.1111/cmi.12981
|View full text |Cite
|
Sign up to set email alerts
|

LAMTOR2/LAMTOR1 complex is required for TAX1BP1‐mediated xenophagy

Abstract: Xenophagy, also known as antibacterial autophagy, plays a role in host defence against invading pathogens such as Group A Streptococcus (GAS) and Salmonella. In xenophagy, autophagy receptors are used in the recognition of invading pathogens and in autophagosome maturation and autolysosome formation. However, the mechanism by which autophagy receptors are regulated during bacterial infection remains poorly elucidated. In this study, we identified LAMTOR2 and LAMTOR1, also named p14 and p18, respectively, as pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Many viruses have thus evolved mechanisms to maintain mTORC1 activity during infection 35 . Recent work has shown that the LAMTOR1/2 proteins may also play important roles in xenophagy 36 .…”
Section: Crosstalk With Other Organelles and Host Protein Machines Cmentioning
confidence: 99%
“…Many viruses have thus evolved mechanisms to maintain mTORC1 activity during infection 35 . Recent work has shown that the LAMTOR1/2 proteins may also play important roles in xenophagy 36 .…”
Section: Crosstalk With Other Organelles and Host Protein Machines Cmentioning
confidence: 99%
“…In addition, they identified LAMTOR2 and LAMTOR1 as previously overlooked xenophagy regulators of TAX1BP1 in response to Salmonella infection, and confirmed that LAMTOR2 was recruited to damaged SCVs via LAMTOR1, an endosomeresident protein. LAMTOR2 was critical for the subsequent recruitment of TAX1BP1, thus accelerating the formation of autolysosomes during bacterial infection (Lin et al, 2019).…”
Section: Adaptors Of Salmonella Autophagymentioning
confidence: 99%
“…Numerous studies have veri ed the signi cance of two signaling pathway in the progression of breast cancer. In addition, Lin and his colleagues have reported that LAMTOR2 interacted with SQSTM1 and was required for recruiting TAX1BP1 to autophagosomes (30). However, to the best of our knowledge, there is no study about the associated between LAMTOR2 and SQSTM1 in breast cancer and the underlying regulation network requires further investigations.…”
Section: Discussionmentioning
confidence: 95%